2005
DOI: 10.1016/j.rmed.2004.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Relation of expired carbon monoxide to smoking history, lapsed time, TLCO measurement and passive smoking

Abstract: We quantified the influence of lapsed time, measurement of gas-transfer factor (TLCO), and passive smoking on expired carbon monoxide (CO) levels, and then evaluated the accuracy of smoking histories against expired CO measurements in patients newly attending 'occupational' compared with 'general' chest clinics. Expired CO levels had an estimated average rate of decline of 3.4 ppm/h in the presumed absence of further smoking, though individual rates depended necessarily on the initial levels (2.1, 3.9, 5.7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Leitch et al [38] concluded that the lapse of 1 h after cigarette smoking and the measurement of D l C O exerted not mild but important influences on the expired CO level, but that passive smoking did not.…”
Section: Discussionmentioning
confidence: 99%
“…Leitch et al [38] concluded that the lapse of 1 h after cigarette smoking and the measurement of D l C O exerted not mild but important influences on the expired CO level, but that passive smoking did not.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the normal smoking condition were required to self-report smoking in their usual manner, verified by a CO measure that was at least 75% of the CO measure obtained in the preliminary session. Participants in the abstinence condition were required to self-report 24-hr tobacco abstinence, confirmed by a CO measure of 4 ppm or less (24-hr cigarette abstinence should result in the near absence of expired CO; Leitch, Harkawat, Askew, Masel, & Hendrick, 2005). Participants in the abstinence condition that did not fulfill all criteria for abstinence were rescheduled for another day.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reports were confirmed by end-expiratory carbon monoxide (CO) measurements using EC50 Micro-Smokerlyzers (BEDFONT, Rochester, UK); 91 participants were excluded because they had an end-expiratory CO of >7 ppm, indicating that they might be smokers. [19][20][21][22] One participant was excluded because of a myocardial infarction in the previous 3 months and four because of digitalis intake in the previous 30 days. None had a cardiac pacer or anaesthesia (narcosis or spinal anaesthesia) in the 8 days prior to the ambulatory ECG recording (Figure 1).…”
Section: Participantsmentioning
confidence: 99%